Distribution of tropomyosin isoforms in different types of single fibers isolated from bovine skeletal muscles. (August 2016) - Oe, M.; Ojima, K.; Nakajima, I.; Chikuni, K.; Shibata, M.; Muroya, S.
Abstract: To clarify the relationship between myosin heavy chain (MyHC) isoforms and tropomyosin (TPM) isoforms in single fibers, 64 single fibers were isolated from each of bovine three muscles (masseter, semispinalis and semitendinosus). mRNA expressions of MyHC and TPM isoforms were analyzed by real-time PCR. All single fibers from the masseter expressed MyHC-slow. The fibers from the semispinalis expressed both MyHC-slow and 2a. The fibers from the semitendinosus expressed MyHC-slow, 2a and 2x. TPM-1 and TPM-2 were co-expressed in 2a and 2x type fibers, and TPM-2 and TPM-3 were co-expressed in slow type fibers. The expression pattern of TPM isoforms in each fiber type was similar between fibers isolated from different muscles. These results suggest that TPM-1 and TPM-3 isoforms correspond to the function of 2a or 2x type fibers and slow type fibers, respectively, with TPM-2 in common. Furthermore, the patterns of MyHC and TPM isoform combinations did not vary among single fibers isolated from the individual muscles examined.